Regulatory Compliance and Best Practice in Archival Accessibility for People with Disabilities in Oman - Mkadmi , Abderrazak; Hamad, Faten (Journal of Ecohumanism, 2025)
The purpose of this study is to assess how accessible archives are for persons with disabilities in Oman, considering the effectiveness of national and international regulations related to this matter, and determining the problems of their implementation. Accordingly, the methodology of the research has been qualitative, combining documentary analysis with semi-structured interviews. The main focus of the documentary analysis is key legislative frameworks which include the Law on Rights of Persons with Disabilities, 2008; the United Nations Convention on the Rights of Persons with Disabilities, also known as CRPD, among other sector-specific regulations. Semi-structured interviews with representatives of five public institutions responsible for disability rights and public services were conducted, including the Ministry of Social Development, the Ministry of Education, the Ministry of Justice and the Children’s Public Library. The results reveal that while Oman has made laudable steps toward establishing a legal framework that ensures the physical accessibility of archives, major gaps can still be identified in the implementation mechanisms related to digital accessibility. Inconsistent enforcement, limited oversight, and the lack of specific regulations relating to archives were identified as major barriers. Those who took part in the consultation emphasized the need for increased awareness and training, coupled with the use of assistive technologies, to promote improved physical and digital access. It concludes that Oman needs to work towards effective enforcement of its regulations and learn from international best practice if it is to achieve full accessibility in archival services.